The Effect of Providing Health Education Using Video Media on Pregnant Women's Knowledge of Hepatitis B in the Work Area of the Melak Health Center - Umi Qalsum; Nilam Noorma; Cristinawati B/R Haloho (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effect of providing health education using video on pregnant women's knowledge about hepatitis B. This type of research is a quantitative study with a quasi-experimental research design with a one group pre-post test design. The population in this study were all pregnant women in the working area of ​​the Melak Health Center in 2022 with a total of 227 people. The sampling technique used was purposive sampling with a total sample of 45 people. The data analysis technique used the Wilcoxon test. Based on the research results obtained, it can be concluded that there is an effect of providing health education using video media on pregnant women's knowledge about hepatitis B in the working area of ​​the Melak Health Center (p value 0.000 <0.05).